Knowledge and attitude of Iraqi pharmacists in Baghdad community toward ‎adverse drug reactions monitoring - Mohammed, Samer Imad; Abdul Al-razaq, Amna Fouad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives:Adverse drug reactions (ADRâ€Žs) can lead to many complications associated with the use of medications .In Iraq where a wide range of medications misused widely due to different reasons, the Iraqi pharmacovigilance program started out few years ago to collect information about adverse drugs reactions and since the success of this program depends on the effective participation of all medical staffs including pharmacists in this program. This study aimed to assess the knowledge, attitude, and degree of awareness of Iraqi pharmacists in Baghdad community toward adverse drugs reactions monitoring and pharmacovigilance program. Methods: This study was a cross-sectional descriptive survey based on individual questionnairethat administered in the English language to a convenience sample of 150 pharmacists working in 3 colleges of pharmacy, 20 community pharmacies and 3 hospitals situated in different areas of Baghdad which are the capital of Iraq. The questionnaire consists of three parts that collect demographic data on the â€Žparticipants and their knowledge, attitudes toward Pharmacovigilanceâ€Ž.Â Results: Although about (62%) of pharmacists have observed ADRs in their practiceâ€Ž only half of the respondents have heard about the term pharmacovigilance, 48% were aware of the national PV program â€Žâ€Ž.Moreover , (â€Ž47.33%â€Ž) of the respondents mentioned that ADRs associated with herbal â€Žproducts should not be reported. Although â€Ž79% of the respondents thought that reporting ADRs is a pharmacist’s duty nevertheless 82% of themÂ â€Žthought that ADRs reporting in Iraq is not widely promoted by the relevant authority .The study showed a high tendency for participation in an adverse drug reactionÂ monitoring program. Interestingly,â€Ž 60% of respondents report that their workplace â€Ždoesn’t encourage them for reporting ADRs, while 48% of respondents indicated that they don’t â€Žhave enough time for reporting ADRs and 38% of them declared their fearing of facing â€Žlegal problem from that .Â â€Ž Conclusion: Iraqi pharmacists although have a high tendency in participation in ADR monitoringÂ program but haveÂ a poor knowledge about pharmacovigilance practices; they lack â€Žunderstanding of the details about the national PV system and ADRs â€Žreporting process and may need more information on how ADRs â€Žreporting are performed.Â Keywords: Knowledge, Attitudes, Adverse drug reactions, Pharmacovigilance.